A Bayesian model for integrating multiple sources of lifetime information in system reliability assessments. - Reese, C. Shane (Journal of Quality Technology)
We present a Bayesian model for assessing the reliability of multicomponent systems. Novel features of this model are the natural manner in which lifetime data collected at either the component, subsystem or system level are integrated with prior information at any level. The model allows pooling of information between similar components, the incorporation of expert opinion, and straightforward handling of censored data. The methodology is illustrated with two examples.